Characterization of Cytomegalovirus Disease in Solid Organ Transplant Recipients by Markers of Inflammation in Plasma - Rollag, Halvor (Public Library of Science, 2013)
BACKGROUND: While several studies have examined the general inflammatory responses in relation to cytomegalovirus infection, the identification of the various inflammatory mediators as well as their relative importance is far from clear. PATIENTS AND METHODS: Solid organ recipients enrolled in an international multicenter trial of cytomegalovirus disease treatment (the VICTOR study) were analyzed (n = 289) (ClinicalTrials.gov NCT00431353). Plasma markers of inflammation and endothelial cell activation were assessed at baseline by enzyme immunoassays. RESULTS: The major findings were: (i) Plasma levels of the CXC-chemokine interferon-inducible protein-10 (P<0.001) and C-reactive protein (P = 0.046) were independently associated with the presence of cytomegalovirus DNAemia above lower level of quantification. (ii) High levels of CC-chemokine ligand 21 (P = 0.027) and pentraxin 3 (P = 0.033) were independently associated with tissue invasive cytomegalovirus disease as opposed to cytomegalovirus syndrome. CONCLUSION: Our findings illustrate the complex interaction between cytomegalovirus and the immune system, involving a wide range of inflammatory mediators that could be associated to disease manifestations in cytomegalovirus related disease.